Performance of MSMEs in India: Issues and Challenges - Bhatnagar , Vishal; Sharma, Dhiraj (Gyan Management Journal, 2016)
Today, all over the world Micro, Small and Medium Enterprises (MSMEs) play an important role in the development of an economy. The role and importance of MSME is very significant towards economic growth, employment generation, exports. MSMEs produce more than 6,000 products range from traditional to high technology items - pearls, metals, electrical, electronic equipment, engineering, pharmaceutical products, chemicals, iron and steel items etc. The MSME support the growth of large industries by providing, components, accessories and semi finished goods required by these industries. WSMEs face a number of problems like poor marketing strategies, bank finance, availability of raw material, non availability of highly skilled labor at affordable cost, low production capacity & ::onstraints in modernization and expansions, logistics problems and lack of power supply. The jefinition of MSME also varies countries to countries. Present paper discusses the major issues and ::hallenges faced by the MSMEs.
Keywords: Advance, Growth; credit deployment performance; total advances